2021
DOI: 10.1177/00472875211064632
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualizing Tourists’ Extraordinary Experiences

Abstract: Research that conceptualizes tourist extraordinary experiences both from the structural and anti-structural perspective is limited in the tourism literature. The purpose of this research is to develop a new theoretical perspective that re-conceptualizes our understanding of tourists’ extraordinary experience by taking into consideration both the structural and anti-structural elements of an experience. It draws on phenomenological interviews with 26 food tourists. The study finds that extraordinary experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…The oldest articles were published in 2006 and focussed on the New Age tourists in New Zealand (Pernecky, 2006), the relationship between the volunteer tourist experience and the long-lasting spiritual experience (Wilson (Zhara, 2006). The latest ones were developed in 2022 and were aimed to examine the concept of craftbeer tourism in Thailand and the meanings attached to it (Chirakranont & Sakdiyakorn, 2022), how tourist-perceived authenticity influences memorability in heritage tourism (Yi et al, 2022), the development of a theoretical perspective about tourists' extraordinary experiences (Goolaup & Nunkoo, 2022) and the benefits of family tourism for parents' and children's wellbeing (Miyakawa & Oguchi, 2022). The supremacy of studies with tourists' samples was impressive (33).…”
Section: Descriptive Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The oldest articles were published in 2006 and focussed on the New Age tourists in New Zealand (Pernecky, 2006), the relationship between the volunteer tourist experience and the long-lasting spiritual experience (Wilson (Zhara, 2006). The latest ones were developed in 2022 and were aimed to examine the concept of craftbeer tourism in Thailand and the meanings attached to it (Chirakranont & Sakdiyakorn, 2022), how tourist-perceived authenticity influences memorability in heritage tourism (Yi et al, 2022), the development of a theoretical perspective about tourists' extraordinary experiences (Goolaup & Nunkoo, 2022) and the benefits of family tourism for parents' and children's wellbeing (Miyakawa & Oguchi, 2022). The supremacy of studies with tourists' samples was impressive (33).…”
Section: Descriptive Characteristicsmentioning
confidence: 99%
“…(Source: Own elaboration) The studies evidenced a few limitations that constitute methodological directions for future investigations. First, there is a need to adopt a mixed methodological approach because the results might be better explored if quantitative and qualitative measures were employed in the same methodological plan (e.g., inductive mixed methods such as focus groups, interviews, surveys and participant observation; e.g., Coudounaris & Sthapit, 2017;Filep, 2014;Goolaup & Nunkoo, 2022;Huang et al, 2020;Laing & Frost, 2017;Sthapit, 2019;Vada et al, 2019aVada et al, , 2019b. Second, longitudinal research should be conducted to uncover all the stages of the experience and monitor the outcomes throughout a period of time (e.g., Bosnjak et al, 2016;Chen et al, 2017;Coghlan, 2015;Miyakawa & Oguchi, 2022;Sthapit & Coudounaris, 2017;Vada et al, 2019aVada et al, , 2019bYi et al, 2022;Yu et al, 2021).…”
Section: Data Analysis Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Zellner et al (2014) and Bj€ ork and Kauppinen-R€ ais€ anen (2019), food characteristics such as presentation and preparation are a journey for the flavour to determine whether the production of prepared dishes is satisfactory for visual appeal or adds up to the flavour of the food. Similarly, tourists may learn about local culture by tasting food prepared with local products and culinary skills (Goolaup and Nunkoo, 2021).…”
Section: Presentation (Simple Access To Food)mentioning
confidence: 99%
“…Factors of this kind require tourists to gain their own experience of trying an attraction's local food (Suntikul et al, 2020). Goolaup and Nunkoo (2021) recently demonstrated that extraordinary tourist experiences from two perspectives (structural and anti-structural) can shape the tourist experience. Thus, this study shows that practitioners have essential insights into the elements that should be assimilated to design the experience scape and provide travellers with an extraordinary experience.…”
mentioning
confidence: 99%